Primary and secondary metabolites of six species of trees, shrubs and herbaceous legumes - Verdecia, D. M.; Herrera Herrera, R. del Carmen; Torres, E.; Sánchez, A. R.; Hernández Montiel, L. G.; Herrera, R. S.; Ramírez, J. L.; Bodas, R.; Giraldéz, F. Jo.; Guillaume, J.; Uvidia, H.; López, S. (Cuban Journal of Agricultural Science, 2021)
Six simultaneous experiments were carried out to determine the content of primary and secondary metabolites of six species of trees, shrubs and forage herbaceous legumes under the edaphoclimatic conditions of Valle del Cauto, Cuba. A randomized block design with six replications was used and the treatments were the regrowth ages of 60, 120 and 180 days for trees and shrubs (Leucaena leucocephala, Tithonia diversifolia, Gliricidia sepium and Eritrina variegata) and 30, 45, 60, 75 and 90 days for creeping legumes (Neonotonia wightii and Teramnus labialis), in the rainy and dry seasons. There were determined N, glucose, fructose and sucrose (primary); total phenols, total tannins, total condensed tannins, total bound condensed tannins, free condensed tannins, alkaloids, flavonoids, saponins, triterpenes, total steroids, stachyose, verbascose and raffinose. Cluster analyzes to group species with similar characteristics were performed. During the rainy season seven groups were found and in the dry season eight; with the best results, comprehensively, for Gliricidia sepium and Tithonia diversifolia in both seasonal periods. The age had a marked effect on the content of primary and secondary metabolites by decreasing the former and increasing the latter as maturity advanced. This performance was evidenced by verifying, through cluster analysis, that the groups where the highest contents of secondary compounds were found were composed of the most advanced ages of the Neonotonia wightii, Teramnus labialis, Erythrina variegata and Leucaena leucocephala species, in both seasonal periods. Aspects of vital importance for future studies where the associative effects of species with lower content of these compounds (Tithonia diversifolia and Gliricidia sepium) were are analyzed, both in the ecosystem and in the animal response. Key words: cluster, dendrogram, nitrogen, oligosaccharides, polyphenols